Level of local cytokine production in the event of nickelid titanium suture material use in experimental surgical hypotension eye operation - A. N. Steblyuk; N. V. Kolesnikova; V. E. Gunter; A. A. Tserkovnaya; S. V. Gunter; O. V. Kokorev; S. G. Anikeev (Кубанский научный медицинский вестник, 2016)
Comparative assessment of cytokine moisture in aqueous chamber with experimental rabbits while use of nickelid titanium suture and in case of traditional suture material in hypotension operations. During the experiment, moisture in aqueous chamber has been studied with 10 adult rabbits, the samples were taken on 3rd, 7th and 30th days and in 3 months after hypotension surgery administered with nickelid titanium suture used as a retention suture. Control group consisted of 5 rabbits, for whom hypotension surgery has been performed with traditional suture material and of 6 intact rabbits. Amount of cytokines in biological fluid (aqueous chamber moisture - ACM) of the animals has been investigated in with enzyme immunodetection method to identify content of cytokines (IL-1β, TNF-α, IL-2, IL-10). The adverse nature of cytokines balance change and quotient of its pro - and anti-inflammatory components in the dynamics after intraocular implantation with TH-10 suture, that indicates positive anti-inflammatory influence of retention suture of nickelid titanium and becomes evident in significant reduction of anti-inflammatory component in cytokine balance, that develops in the farthermost monitoring terms, as well as in clinically unresponsive post-operative course with animals of test group compared to comparison group.